Fundamental motor skills, executive functions, and academic achievement of Chinese schoolchildren: Testing a mediating model - Lijing Wang; Jiancui Sun; Lijuan Wang; Danheng Zheng; Yulan Zhou (PLoS ONE, 2025)
Background Researchers have observed the relationship between children’s fundamental motor skills (FMS) and their academic achievement. However, the inner workings of this correlation remain underexplored, especially in the context of China. This study addresses this gap by investigating the associations among FMS, such as locomotor, object control, and stability skills, executive function (EF), such as inhibition control and working memory, and academic achievement among Chinese schoolchildren. Furthermore, this research determines how EF mediates the relationship between FMS and academic achievement and whether gender and age moderate the mediating process. Method This research involved 733 primary schoolchildren aged 6–12 years from China. First, the Test of Gross Motor Development-Third Edition and the Körperkoordinationstest Für Kinder were used to measure FMS. Then, the Childhood Executive Functioning Inventory was employed to evaluate EF, while standardized written examinations in Chinese and mathematics subjects were used to determine academic achievement. Results Regression analyses were conducted. Results revealed that the children’s performance in Chinese was negatively correlated with their working memory ( β = −0.129, p = 0.005) and inhibition control ( β = −0.191, p < 0.001) but positively linked to object control ( β = 0.198, p < 0.001). Meanwhile, children’s performance in mathematics had a negative relationship with inhibition ( β = −0.246, p < 0.001) but positive relationships with object control ( β = 0.095, p = 0.009) and stability skills ( β = 0.096, p = 0.010). In addition, a mediation analysis was conducted. Results revealed that EF had a partially mediating effect on the relationship between FMS and academic achievement in Chinese ( β = 0.110, 95% CI [0.051, 0.175]) and mathematics ( β = 0.134, 95% CI [0.070, 0.189]). In the mathematics model, it is only found that age significantly and negatively moderates the path between EF and mathematics ( β = −0.627, 95% CI [−0.698, −0.332], p < 0.001). Conclusions This study highlights the critical role of FMS and EF in Chinese schoolchildren’s academic achievement. The outcomes of this work suggest that educators can bolster FMS and EF through well-crafted, engaging, and encouraging interventions or programs. In turn, these designs can support the academic achievement of schoolchildren. Strategies aimed at improving object control can foster children’s performance in Chinese and mathematics. Meanwhile, programs focused on developing stability skills can be implemented to enhance performance in mathematics, especially for younger primary schoolchildren.